Spark plasma processing of semi-conductive titanium carbide dispersed alumina composites. Issue 1 (2nd January 2022) - Ram Prakash, S.; Selvakumar, G.; Rajkumar, K.
ABSTRACT: The spark plasma sintering behavior of the alumina ceramic composite that is modified by the spatial distribution of electrically semi-conductive sub-micron scale titanium carbide particles was investigated. Titanium Carbide was reinforced to the alumina composites in different weight percent concentrations of 20, 25, 30, and 35. The influence of titanium carbide particle distribution on the thermal profile, micro-hardness, and wear resistance of alumina ceramic composites was studied. Homogenous spatial distribution of sub-micron scale semi-conductive titanium carbide particles in the composite were noticed through scanning electron microscopy, excluding the 35 weight percent sintered sample. In the spark plasma sintering processed samples, X-ray diffraction results revealed strong α-alumina and titanium carbide peaks. The obtained experimental results show that a higher titanium carbide concentration causes an earlier onset of shrinkage temperature, which positively impacts densification. The addition of titanium carbide particles accelerates the sintering kinetics and improves the properties. Among all composites, the sample with 30 weight percent has the highest relative density of 98.80% and hardness of 20.56 GPa. Besides, the highly densified sample of 30 weight percent has superior wear resistance to all other composites, and can be used for high-temperature sliding applications.